DFT/TD-DFT study of ruthenium bipyridyl-based dyes with a chalcogen donor (X = S, Se, Te), for application as dye-sensitized solar cells. (8th May 2017) - Bourouina, Assia; Rekhis, Mâammar; Trari, Mohamed
Graphical abstract: The structural and electronic properties of the derivatives of ruthenium-based dyes designed for use as sensitizers in DSSCs were investigated by DFT and TD-DFT methods for a donor ligand that enhances the dye performance in dye-sensitized solar cells. Going from the sulfur to tellurium derivatives, a bathochromic red shift is observed in the absorption spectra of the proposed dyes. Abstract: In the present work, the structural and electronic properties of the derivatives of ruthenium-based dyes designed for use as sensitizers in DSSCs were studied using DFT and TD-DFT methods. In order to design novel ligands that improve the dye performances in dye-sensitized solar cells, we replaced the S atom in the C2 N2 S2 donor ligand moiety with Se or Te atoms; six derivatives dyes (systems 2, 3, 5, 6, 8 and 9) were theoretically designed. Beside the influence of chalcogen atom in the ligand donor set on the electronic properties, the effect of the functional groups (–H, –COOH and –COOEt) attached to the bipyridyl unit in the acceptor ligand has been also discussed. The absorption maxima of the proposed dyes have been compared to those of the ruthenium-based dye containing sulfur, for which experimental data are available. A significant impact is noticed in the energy transition by the substitution of selenium or tellurium atoms instead of the sulfur atom, with a decrease in the gap energy. Going from sulfur to tellurium, a bathochromic red shift is observed in the absorption spectra of the proposed dyes. By calculating and analyzing the photovoltaic parameters of the light harvesting efficiency ( LHE ), open circuit photovoltage ( V oc) and electron injection driving force (∆ G inject ), it is suggested that among the proposed systems, the systems 5 [Ru(COOHbpy)2 N2 C2 Se2 ] and 8 [Ru(COOEtbpy)2 N2 C2 Se2 ] are promising for the design of new sensitive dyes in solar cells.